Teachers’ interpretations of questioning practices to enhance critical thinking in Grade 10 financial mathematics - Zondo, Ayanda; Mbhiza, Hlamulo Wiseman (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study investigates how Grade 10 mathematics teachers interpret and enact their questioning strategies to promote critical thinking in financial mathematics classrooms. Specifically, it identifies the types of questions teachers employ, examines the rationales underlying their choices, and analyses how these questioning practices shape opportunities for learners’ critical reasoning. Method: A qualitative multiple-case study design was adopted involving six purposively selected teachers from three public secondary schools in Pinetown, KwaZulu-Natal. Data were generated through semi-structured questionnaires, classroom observations, and interviews. Inductive thematic analysis was conducted, guided by the Revised Bloom’s Taxonomy and the Cognitive Rigor Matrix to categorise the cognitive demands embedded in teachers’ questions. Findings: The findings reveal that teachers employed five types of questions: factual, procedural, open-ended, probing, and adaptive. While all teachers relied heavily on lower-order questioning, only some consistently used higher-order questions. Teachers who incorporated open-ended and adaptive questions created richer cognitive engagement, enabling learners to justify reasoning and explore conceptual connections. By contrast, teachers who relied solely on factual and procedural questions provided limited opportunities for critical thinking to emerge. Significance: This study underscores the pivotal role of higher-order questioning in strengthening critical thinking within financial mathematics instruction. The results highlight the need for targeted professional development that equips teachers to design and implement cognitively demanding questions. Such support is essential for advancing learner engagement, deepening conceptual understanding, and enhancing the overall quality of mathematics teaching in secondary schools.